Penerapan Diksi Bahasa Jurnalistik pada Berita Kriminal Asusila di Surat Kabar Samarinda Pos - Belinda Rizky; Abdullah Karim; Nurliah Nurliah (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2020)
This study aims to determine, describe, and analyze the application of journalistic language diction in the Teun A. van Dijk analysis model on criminal news of immoral types on the front page of the Samarinda Pos newspaper in October 2017 edition. The method used in this study is a descriptive qualitative method, using the Teun A. van Dijk discourse analysis model. The results of this study indicate that from the text dimension, the use of diction or choice of words is straightforward, concrete and specific. But also found diction that is general and worth the taste. From the dimension of social cognition, Samarinda Pos editors construct immoral criminal reporting based on event schemas by prioritizing the selection of diction which does not have a legal and pro-‐‑market impact. From the dimension of social analysis, the influence of power and access can be seen through comments and leads that tend to use vulgar language that potentially marginalizes women.